Tourism assistance through an example of content innovation programs at Kedung Gajah Sentolo: A robot demonstration. - Surahmat, Indar; Rustan, Ikbar Kausar; Kusuma, Satria Giri (Journal of Community Service and Empowerment, 2023)
The recovery programs of a tourism sector attract huge attention currently. After relaxation of travel restrictions, tourism stakeholders carry out some crucial actions. It includes the concept of participation of local authorities and residents. They formed groups of people who care about tourism “pokdarwis (kelompok sadar wisata)”. Some community service programs have also contributed to the development. Those programs mostly provided training for tourism stakeholders such as managing a tourist attraction and digital marketing. Rarely, the program includes a real case of tourism content innovation how to attract visitors. This community service program took place in “Kedung Gajah” in Sentolo village and in collaboration with Pokdarwis Gerbang Sentolo. As a new tourism object, Kedung Gajah Sentolo requires some views of content innovation, and its operator needs to expand its visitor number. Therefore, this program was intended to provide an assistance to solve both problems. But, beside an assistance, this program also gave a real event. Three main steps were done including observations, coordination between the community service team and the operator of Kedung Gajah and performing a robot demonstration. The observation step resulted some recommendation on the development of Kedung Gajah. Furthermore, in the period of preparation, at least five meetings were conducted to exchange and share information. Finally, the robot demonstration could attract more than 500 people visited the object and these visitors gave benefit to the turnover more than five million rupiah from culinary in estimation.